1982
DOI: 10.1001/archotol.1982.00790520008003
|View full text |Cite
|
Sign up to set email alerts
|

Late Changes in Ear Canal Volumes After Mastoid Obliteration

Abstract: \s=b\In this study, preoperative and postoperative ear canal volumes of ears subjected to obliterative radical mastoidectomy were assessed. The measurements were performed using sterile saline solution both at the preoperative stage (V0) and at the early (one year, V,) and the late (five to 13 years, V2) postoperative stages. The mean V0 was 0.8 mL (SD, 0.2 mL); V1, 1.0 mL (SD, 0.3 mL); and V2, 1.2 mL (SD, 0.4 mL). The differences were highly significant. Clinically, the widening of the ear canals was mainly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In a study where Palva flap was used for mastoid obliteration, the ear canal was found enlarged at both the early and the late postoperative check-up compared to the preoperative values [11]. The results of the studies, reported by Kahramanyol et al [8] in which mastoid cavities were obliterated with fascioperiosteal flap, have shown that the mastoid cavity volume was decreased by 39% due to neo-osteogenesis under fascioperiosteal flap, and that the obliteration has stayed in long term has shown radiologically [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study where Palva flap was used for mastoid obliteration, the ear canal was found enlarged at both the early and the late postoperative check-up compared to the preoperative values [11]. The results of the studies, reported by Kahramanyol et al [8] in which mastoid cavities were obliterated with fascioperiosteal flap, have shown that the mastoid cavity volume was decreased by 39% due to neo-osteogenesis under fascioperiosteal flap, and that the obliteration has stayed in long term has shown radiologically [9].…”
Section: Discussionmentioning
confidence: 99%
“…These patients need life-long otologic care for the debris that accumulates due to the insufficient self-cleaning mechanism of mastoidectomy cavities. Sixteen percent of ears without cavities needs cleaning, whereas this ratio climbs to 42% for ears with cavities [11]. These patients complain of dizziness in cold weather and during swimming.…”
Section: Introductionmentioning
confidence: 99%
“…However, the resulting radical cavities can be troublesome . Self‐cleansing mechanisms of the osseous external auditory canal (OEAC) are disrupted, leading to frequent consultations with otorhinolaryngologists . A multifactorial etiology has been proposed and revision surgery has proven to be very effective .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 It has been reported that flaps wither away in time. 20,21 Kahramanyol and coworkers have shown that a flap properly nurtured by an artery and supported by periosteum does not wither away, but gets strong in time. 18,19 Our experience and findings, the flap fills the cavity with not only its mass but an increased bone volume in time by the neo-osteogenesis, supports the same idea.…”
Section: Discussionmentioning
confidence: 99%